Programming with Java - Bhave, Mahesh P., 1957- (Pearson Education : Dorling Kindersley (India), 2009)
Programming with Java is designed to help the reader understand the concepts of Java programming language. It includes an exhaustive coverage of additional appendices on keywords, operators and supplementary programs; additional chapters on Collect.